A new langmuir-schaefer-based method developed for catalytic studies of acetylcholinesterase in planar fiolms of erythrocyte membranes - Felsztyna, I. (2017)
Fil: Felsztyna, I. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina.